Application of intraoperative hypothermic saline to relieve postoperative pain for pediatric coblation tonsillectomy. (October 2020) - Lu, Yingxia; Dong, Yuke; Wang, Zhan; Liang, Jieqiong; Gao, Yan; Ye, Pengfei
Abstract: Objectives: To evaluate the effect of hypothermic saline application for pediatric coblation tonsillectomy on postoperative pain. Methods: Forty-eight children with adenotonsillar hyperplasia underwent tonsillectomy ± adenoidectomy. 24 children were in the HTS group (which used hypothermic saline as the coblation medium in operation), the other 24 children with the same age were in the control NTS group (who use normothermic saline as the coblation medium). All children and their parents were asked to complete a daily questionnaire for 7 days following their surgery. Results: Significant differences were observed when comparing the two outlet water temperatures of the coblation wand both at ablation power and at coagulation power ( p = 0.000). Children in HTS group got lower scores than those in the NTS group ( p < 0.05). No side effects were observed. Conclusions: Using hypothermic normal saline as the media of coblation wand is potential for reduce postoperative pain in pediatric patients while also having no detrimental financial or medical effects on said patients.